Coordination and organization: The two dimensions of nonliberal capitalism - Martin Höpner (Max Planck Institute for the Study of Societies, 2007)
This paper suggests a two-dimensional concept of nonliberal capitalism: coordinated capitalism (as described in the varieties of capitalism framework) and organized capitalism. While the coordination function of institutions canalizes individual maximization strategies of firms in order to adjust for collective action problems, the organization function transcends maximization strategies and adjusts them to collective interests beyond maximization. Political economies are highly organized when firms are not only the private business of owners and insiders but, in addition, quasi-public infrastructures and, therefore, highly constrained in their economic decisions by institutionally sanctioned collective interests (such as sectoral interests, class interests, or political interests). I construct an index on organized capitalism by combining data on ownership structures, board level codetermination, the density of employers' associations and trade union density in order to allow for comparison between varying extents of coordination and organization in 20 OECD countries. The German example is used to demonstrate the analytical usefulness of the coordinationorganization distinction in qualitative terms. The distinction allows for differentiation between two forms of liberalization: declining coordination and disorganization.
Keywords: 300; Wirtschaftsordnung; Kapitalismus; Eigentümerstruktur; Mitbestimmung; Arbeitsbeziehungen; Korporatismus; Deregulierung; OECD-Staaten; Deutschland